Impactos químicos, biológicos e ecológicos de agrotóxicos e metais pesados em solos da Serra da Ibiapaba, Ceará - Martins, Thais da Silva (2024)
Contamination of agricultural soils by pesticides and heavy metals (HM) represents a serious environmental threat, especially in tropical regions such as Brazil, where intensive use of pesticides is common. Soil enzymes, essential for nutrient cycling and soil health, can be affected by these contaminants, compromising fertility and microbial activity. However, the combined effects of HM and pesticides on enzymatic activity are still poorly understood, despite their potential negative impact. This study proposes that prolonged use of pesticides increases the concentration of heavy metals in the soil, reducing enzymatic activity and altering nutrient cycling. Furthermore, the duration of cultivation and the seasonal period are considered to influence the concentration of residues in the soil. We aimed to investigate the effects of intensive use of pesticides and contamination by heavy metals on soil quality, with emphasis on enzymatic activity and residue persistence over time and under different seasonal conditions. We analyzed the presence of 45 pesticides and their interaction with HM in soils from flower cultivation areas with different exposure times (5 and 10 years) and in a native forest area in São Benedito, CE, during the dry and rainy seasons. We quantified the concentrations of Cd, Cu, Mn, Pb and Zn, and used ecological risk indices to evaluate contamination levels and enzymatic activity (arylsulfatase, β-glucosidase, acid phosphatase, urease). The results indicated the negative effects of soil contamination on the soil microbiota, with the highest concentrations of HM and pesticides observed in the cultivated area for the longest time, mainly in the dry season. The presence of pesticides was also detected in the native forest area, indicating the persistence and transport of these compounds beyond the cultivated areas. The total concentration of pesticides varied between periods, with 1,028.73 ng g-1 in the rainy season and 4,793.95 ng g-1 in the dry season, reflecting an increase in residues in the dry season. The herbicide pendimethalin presented the highest average concentration in the cultivated area 10 years ago, with 356.80 ng g-1. The presence of organophosphates was negatively correlated with the activity of arylsulfatase and urease, indicating a reduction in soil quality due to the interference of these compounds in biochemical processes. A positive correlation was observed between organophosphates and the activities of β-glucosidase and acid phosphatase, suggesting complex effects. Furthermore, there were negative correlations between HM (especially Cu, Mn and Zn) and arylsulfatase activity, and a reduction in urease in the presence of Cd. Enzyme stoichiometry in cultivated areas demonstrated an increase in vector length, indicating that Cd, Cu, Mn and Zn increase microbial carbon limitation. The continuous introduction of pesticides increases HM contamination levels and compromises enzyme activity, affecting the soil's ability to sustain essential ecological processes. This study highlights the urgency of guidelines to mitigate the impacts of contamination on soils, protecting agricultural sustainability and soil health in the long term.